Bharatakhaṇḍamuna Āṅglarājyasthāpana : Tārens anu Pārlameṇṭusabhyunicē vrāyabaḍina "Empire in Asia" anu granthamunaku Āndhrīkaraṇamu - McCullagh Torrens, W. T. (William Torrens), 1813-1894 (SAMP early 20th-century Indian books project ;, 1936)
History of the British occupation in India.